The principles and practice of effective leadership - Zinkin, John (De Gruyter, 2021)
This thought-provoking and timely book asserts that the dichotomy between leaders and managers described in much business literature fails to recognize how the two roles overlap. The book discusses techniques for senior executives based on history and neuroscience to enhance their "managerial leadership" in different environments. The ethical dilemmas of directors and executives are explored, with lessons from both leadership failures and successes. The Principles and Practice of Effective Leadership redefines "leadership" as a morally neutral activity, reflecting the impact of strategic, cultural and operational contexts on a leader's effectiveness. The authors suggest there are universal but morally neutral techniques for effective leadership that depend on the context in which they are practiced. In Part 1, the careers and personalities of historical figures including Elizabeth Tudor, Napoleon, and Atatürk are examined. Part 2 deliberates on why leadership cannot be separated from effective management and concludes that leadership is managerial, and best encapsulated in the concept of "wayfinding." In Part 3, the authors discuss the techniques "wayfinders" can learn to be both effective and ethical, using a simple and practical framework. This insightful book is essential reading for professionals, coaches, consultants, and academics interested in techniques and ethics of leadership and executive education.